Gestión administrativa y su efecto en la rotación del personal de la empresa menestras del negro, Quevedo, año 2023 - Valencia Cabrera, Mónica Margarita (2025)
This research was conducted at the company Menestras del Negro in the Quevedo canton, with the objective of evaluating administrative management and its impact on employee turnover. A mixed-method approach was applied, incorporating field, descriptive, and documentary research, using inductive, deductive, and statistical methods. The sample included 24 participants, such as the manager, current employees, and former employees, who were surveyed and interviewed for data collection. The results showed that although the company maintains a functional administrative structure based on planning, organizing, directing, and controlling, it experienced a high employee turnover rate of 77% in 2023. This situation is linked to temporary contracts, high work pressure, limited compensation relative to seniority, and an organizational climate marked by poor communication and few development opportunities. In addition, the company incurred significant turnover-related costs and retained only 23.08% of its key personnel. According to current and former employees, weaknesses were noted in performance recognition, emotional support, and promotion opportunities. The validity of the data was confirmed by a high Spearman’s Rho correlation coefficient of 0.936, indicating a strong positive relationship between administrative management and employee turnover, highlighting the urgent need to improve retention strategies and the workplace environment.